Maternal anxiety and depression and development of prematurely born infants in the first year of life - Vita Carvalho, Ana Emilia; Eulógio Martinez, Francisco; Martins Linhares, Maria Beatriz (The Spanish Journal of Psychology, 2008)
The purpose of this study was: (a) to assess and to compare anxiety and depression symptoms in mothers of preterm neonates during hospitalization in the Neonatal Intensive Care Unit, after discharge, and at the end of the infants’ first year of life; and (b) to assess the child’s development at 12 months of chronological corrected age (CCA). Thirty-six mothers, with no psychiatric antecedents assessed with the SCID-NP, were evaluated by STAI and BDI. The infants were assessed with Bayley-II Scales. There was a significant decrease in clinical symptoms of state-anxiety in mothers (p = .008), comparing the period during hospitalization and after discharge of the infants. Clinical symptoms of anxiety and depression were observed in 20% of the mothers at the end of the infants’ first year of age. The majority of the infants exhibited normal development on Bayley-II at 12 months CCA; however, 25% of the infants displayed cognitive problems and 40% motor problems. The mothers’ anxiety and depression symptoms decreased at the end of the first year of life of the pre-term infants and the children showed predominately normal development at this phase.